1967
DOI: 10.1080/00268976700100161
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine and proton spin absorption and relaxation in solid ammonium heptafluozirconate

Abstract: H 1 magnetic resonance absorption in (NH4)aZrF7 has been studied over the temperature range 20 ~ to -196~A line width transition due to low activation energy reorientations of two types of NH4 + ion was observed. The fluorine absorption data give also evidence of reorientation of zirconiumfluorine complex. The transient experiment carried out at 15-3 and 22.9 Mc/sec in the same temperature interval supports the absorption results by indicating conclusively that two motions are effective in the crystal studied.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1970
1970
1982
1982

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Therefore it is reasonable to expect reorientation processes at elevated temperatures. This assumption is strongly supported by the results of Pintar et al [9], who investigated the isomorphous Zrcompounds by NMR.…”
Section: N(180 ~ T)-n(90 ~ T) a 2 G22(t ) =2 N(180o ' T)+2n(90~ ' T) (2)mentioning
confidence: 64%
See 1 more Smart Citation
“…Therefore it is reasonable to expect reorientation processes at elevated temperatures. This assumption is strongly supported by the results of Pintar et al [9], who investigated the isomorphous Zrcompounds by NMR.…”
Section: N(180 ~ T)-n(90 ~ T) a 2 G22(t ) =2 N(180o ' T)+2n(90~ ' T) (2)mentioning
confidence: 64%
“…These results are also in striking agreement with NMR measurements at 19F in the isomorphous Zr-compound. Pintar et al [9] related the temperature dependence of the line shape to a relaxation behaviour, which should be caused by an activation process with an activation energy of 8 (2) kcal/ mole corresponding to 0.35 (8) eV.…”
Section: The Relaxation Spectramentioning
confidence: 99%
“…Nuclear magnetic resonance studies have shown that the ZrF~-ions and NH + ions in (NHa)3ZrF7 are dynamically disordered and reorienting (Blinc & Lahajnar, 1967;Pintar, Lahajnar & Slivnik, 1966). The present neutron study was begun to determine the nature of the disorder of the ammonium ions.…”
Section: Introductionmentioning
confidence: 93%